Training Mendeley Application and Strategy for Writing Scientific Articles - Ariestika, Elsa; Hita, I Putu Agus Dharma; Pranata, Doni; Alamsyah, Nur Fadly; Valentri, Avi; Nanda, Fitri Agung (Universitas Teknokrat Indonesia, 2024)
This scientific article emphasizes the important role of individual researchers in contributing to the development of science and technology on a wider scale. The strategy for writing scientific papers is an innovation in writing with research trends. Scientific papers also relate to tools with applications such as Mendeley. While Mendeley serves as a valuable reference management tool, limited knowledge and skills among researchers can pose significant obstacles. This article highlights the importance of in-depth understanding and optimal use of the Mendeley tool, and proposes training initiatives to improve the digital literacy of researchers in the strategy of writing scientific papers.